PENYAJIAN LAPORAN KEUANGAN PEMKOT SURABAYA DALAM PENERAPAN PP NO. 71 TAHUN 2010 - Gita Desipradani; Zeni Rusmawati (UMSurabaya Publishing, 2017)
ABSTRACTChanges in the field of government accounting should be based on a strong foundation that is with the Government Accounting Standards (SAP). With the issuance of PP No.71 Year 2010 on SAP can be used to produce a reliable financial report and can be used as benchmarks and standards in decision making within the scope of government. The presentation of financial statements in accordance with SAP is useful for the creation of accountability and transparency of government financial management. This study aims to find out how the presentation of the financial statements of the Government of Surabaya City in the application of PP. 71 Year 2010 as well as accountability and transparency of presentation of financial statements of Surabaya City Government. The research method used descriptive qualitative. The result of this research, presentation of financial report of Surabaya City Government has been made based on PP. 71 Year 2010, although the constraints occurred in the process of presentation, but the accountability and transparency of the Government of Surabaya is useful in making decisions for those who need local financial information.Keywords: Presentation of Financial Statement, PP. 71 Year 2010, Accountability, TransparencyCorrespondence to : gitadesip@gmail.com, u_zeni@yahoo.co.idABSTRAKPerubahan dibidang akuntansi pemerintahan harus didasari dengan suatu dasar yang kuat yaitu dengan adanya Standar Akuntansi Pemerintahan (SAP). Dengan diterbitkannya PP No.71 Tahun 2010 tentang SAP dapat digunakan untuk menghasilkan suatu laporan keuangan yang andal serta dapat dijadikan patokan dan standar dalam pengambilan keputusan dalam lingkup pemerintahan. Penyajian laporan keuangan sesuai dengan SAP bermanfaat untuk terciptanya akuntabilitas dan transparansi pengelolaan keuangan pemerintahan. Penelitian ini bertujuan untuk mengetahui bagaimana penyajian laporan keuangan Pemerintah Kota Surabaya dalam penerapan PP No. 71 Tahun 2010 serta akuntabilitas dan transparansi penyajian laporan keuangan Pemerintah Kota Surabaya. Metode penelitian menggunakan deskriptif kualitatif. Hasil penelitian ini, penyajian laporan keuangan Pemerintah Kota Surabaya sudah dibuat berdasarkan PP No. 71 Tahun 2010, meskipun kendala terjadi dalam proses penyajiannya, namun akuntabilitas serta transparansi keuangan Pemerintah Kota Surabaya bermanfaat dalam pengambilan keputusan bagi pihak-pihak yang membutuhkan informasi keuangan daerah.Kata kunci : Penyajian Laporan Keuangan, PP No. 71 Tahun 2010, Akuntabilitas, TransparansiKorespondensi : gitadesip@gmail.com, u_zeni@yahoo.co.id